2018
DOI: 10.1016/j.shaw.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation into Urinary 1-Hydroxypyrene as a Biomarker for Polycyclic Aromatic Hydrocarbons exposure among Charcoal Workers in Ogun and Oyo States, Nigeria

Abstract: BackgroundUrinary 1-hydroxypyrene (1-OHP) has been widely used as a biomarker of polycyclic aromatic hydrocarbons (PAHs) in occupationally exposed workers. The objective of this study is to investigate the concentration of urinary 1-OHP among charcoal workers as subjects and non-charcoal workers as controls.MethodsEarly morning urine samples were collected from 68 persons (25 charcoal workers in Igbo-Ora, 20 charcoal workers in Alabata, and 23 non-charcoal workers) who volunteered to participate in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Titcombe et al [43] reported mean total PAH and benzo(a)pyrene levels of 5040 ± 909 ng/m 3 and 767 ng/m 3 , 334 ± 57 ng/m 3 and 44 ng/m 3 , and <1 ng/m 3 and 0 ng/m 3 in open firewood, charcoal and LPG users, respectively. Charcoal production was associated with higher levels (>0.49 µmol/mol creatinine) of urinary1hydroxypyrene (RR: 3.14, 95% CI: 1.7-5.8, P < 0.01) [18]. Awopeju et al [38] reported median (interquartile range) benzene concentration of 119.3 (82.7-343.7) and 0.0 (0.0-51.2) in passive samplers worn by street cooks and non-street cooks, respectively.…”
Section: Exposure To Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
See 4 more Smart Citations
“…Titcombe et al [43] reported mean total PAH and benzo(a)pyrene levels of 5040 ± 909 ng/m 3 and 767 ng/m 3 , 334 ± 57 ng/m 3 and 44 ng/m 3 , and <1 ng/m 3 and 0 ng/m 3 in open firewood, charcoal and LPG users, respectively. Charcoal production was associated with higher levels (>0.49 µmol/mol creatinine) of urinary1hydroxypyrene (RR: 3.14, 95% CI: 1.7-5.8, P < 0.01) [18]. Awopeju et al [38] reported median (interquartile range) benzene concentration of 119.3 (82.7-343.7) and 0.0 (0.0-51.2) in passive samplers worn by street cooks and non-street cooks, respectively.…”
Section: Exposure To Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…Concentrations of PAHs were measured in three studies [18,38,43]. Titcombe et al [43] reported mean total PAH and benzo(a)pyrene levels of 5040 ± 909 ng/m 3 and 767 ng/m 3 , 334 ± 57 ng/m 3 and 44 ng/m 3 , and <1 ng/m 3 and 0 ng/m 3 in open firewood, charcoal and LPG users, respectively.…”
Section: Exposure To Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
See 3 more Smart Citations